REKONSTRUKSI PEMBELAJARAN BAHASA ARAB MODERN MELALUI PEMIKIRAN MAHMUD KAMIL AN-NAQAH: INTEGRASI PENDEKATAN KOMUNIKATIF, KETERAMPILAN BERBAHASA, DAN KURIKULUM BERBASIS PENGALAMAN - Nugroho Widi Susanto; Ilham Noor; Adi Maryadi (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze Mahmud Kamil An-Naqah's contributions to the development of modern Arabic language teaching methodology by reconstructing pedagogical concepts oriented toward communicative competence. Employing a qualitative approach with a library research design, data were collected through documentation of Mahmud Kamil An-Naqah's major works as the primary source, supplemented by scholarly books and journal articles as secondary sources. The data were analyzed using content analysis through systematic stages of unitization, data reduction, categorization, interpretation, and inference. The analysis focused on the principles of the communicative approach, the integration of the four language skills, and the curriculum development components proposed by Mahmud Kamil An-Naqah, as well as their relevance to contemporary Arabic language education. The results reveal that Mahmud Kamil An-Naqah conceptualizes language as a medium of social communication, shifting Arabic language instruction from a grammar-oriented paradigm toward the development of communicative competence through the integrated teaching of listening, speaking, reading, and writing skills. Furthermore, curriculum development is grounded in learners' language experiences, the characteristics of the Arabic language, learners' psychological conditions, socio-cultural dimensions, and the utilization of technology to provide authentic language input. The novelty of this study lies in the systematic reconstruction of Mahmud Kamil An-Naqah's educational thought within the context of digital-era Arabic language education. The findings strengthen the theoretical foundation of communicative Arabic language teaching while offering practical implications for educators and curriculum developers in designing more interactive, contextualized, and adaptive Arabic language learning aligned with contemporary educational demands.